2012
DOI: 10.1016/j.cap.2011.09.011
|View full text |Cite
|
Sign up to set email alerts
|

High mobility organic thin-film transistors on plastic substrate

Abstract: Chapter 1General Introduction Chapter 2 Development of Heteroaromatic-Fused TTFs as Organic Semiconductors for Solution Processible Field-Effect Transistors 2.1 Introduction for Organic Semiconductors 2.2 Bis(N-alkyl-pyrrolo[3,4-d])tetrathiafulvalenes (N-alkyl-PyTTFs) 2.3 Bis(N-acyl-pyrrolo[3,4-d])tetrathiafulvalenes (N-acyl-PyTTFs) 2.4 Bis(thieno[2,3-d])tetrathiafulvalenes (αDT-TTFs) 2.5 Correlation between Electronic Structure in Solid State and Field-Effect Mobility 2.6 Conclusion for Chapter 2 Chapter 3 Ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 94 publications
0
9
0
Order By: Relevance
“…On the PI-C 0 (see Figure S18a), C 10 -DNTT grains exhibited “wire-like” crystalline grains. Due to the presence of these “wire-like” grains, the C 10 -DNTT TFT shows the lowest average mobility of just 0.31 cm 2 /Vs . However, as the alkyl chain length of PI increases, the C 10 -DNTT grown on the PI-C 10 surface shows a mixed morphology in Figure S18b, which will be referred to as “wire-like” and “rod-like”; thus, the average mobility is increased to 0.70 cm 2 /Vs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the PI-C 0 (see Figure S18a), C 10 -DNTT grains exhibited “wire-like” crystalline grains. Due to the presence of these “wire-like” grains, the C 10 -DNTT TFT shows the lowest average mobility of just 0.31 cm 2 /Vs . However, as the alkyl chain length of PI increases, the C 10 -DNTT grown on the PI-C 10 surface shows a mixed morphology in Figure S18b, which will be referred to as “wire-like” and “rod-like”; thus, the average mobility is increased to 0.70 cm 2 /Vs.…”
Section: Resultsmentioning
confidence: 99%
“…Different alkyl side chains modification strategies ,, are often applied to organic semiconductor systems to improve their solubility and flexibility as well as adjust the molecular microstructure and charge transport behavior. Meanwhile, some researchers also elaborated on the effect of gate dielectrics based on metal or metal oxide surfaces with different alkyl chains length self-assembled monolayers on the device performance and stability of OTFTs. , These results proved that the alkyl chains’ chemical modification strategies in both organic semiconductors and inorganic dielectric layers can significantly influence the device performance.…”
Section: Introductionmentioning
confidence: 99%
“…To conquer oxidization in air for OSC like pentacene, an airstable and high-performance OSC, DNTT with mobility of as large as 2.1 cm 2 /(V s) on PEN substrate was reported by Zschieschang et al [24], which showed excellent stability for periods of several months of storage in ambient air. Alkyl-substituted DNTT, C 10 -DNTT showed an enhanced mobility of 2.4 cm 2 /(V s) and a high on/off ratio of 10 7 on PC substrate under ambient conditions after annealing at 100°C in N 2 atmosphere for 1 h with a channel length of 190 lm and width of 1,500 lm [21].…”
Section: P-type Osc Materialsmentioning
confidence: 99%
“…Often, additional processing steps are required to deposit planarization layers. 5 Also, OFETs on plastic substrates can perform inferiorly as compared to those on rigid Si/SiO 2 substrates 6 since the morphology of the semiconductor thin film can be strongly affected by different underlying surfaces. In order to realise low-cost and mass-produced devices, it is imperative to investigate cheap and easily-processable semiconductors and insulators, the main components of organic field-effect transistors (OFETs), that can be applied on plastic substrates.…”
mentioning
confidence: 99%